Pneumomediastinum in COVID Era: A case series - Kashish Dutta; Deepak Aggarwal; Mandeep Sodhi; Surabhi Jaggi; Varinder Saini (The Journal of Association of Chest Physicians, 2023)
Subcutaneous emphysema and pneumomediastinum are uncommon complications seen in COVID −19 patients that tend to worsen their prognosis. Being a new disease, management of this new complication of this disease is not well defined in the literature. We present a case series of six patients of probable/confirmed COVID who developed pneumomediastinum at varied time intervals from the onset of symptoms. Timely recognition and management led to recovery in all of them. Management done in this case series may help in providing data to formulate treatment guidelines for this potentially fatal disease.